Investigations on the turbulence resistant characteristics of Custom Designed Beams embedded with multiple phase singularities. (February 2020) - Dixit, Awakash; Kumar Mishra, Sanjay; Kumar Gupta, Arun
Highlights: Custom Designed Beams are explored to study their turbulence resilence behaviour. Generation and propagation of these CDB are studied in free-space & turbulence. Turbulence is simulated with the help of two types of simulators (ATS & TC) in lab. Offline video processing methodology is used to compute the performance parameters. Effectiveness of beams is studied in terms of beam deformation & scintillation index. Abstract: Investigation on the propagation of an optical beam carrying phase singularities through atmospheric turbulence attracts researcher involved in the laser projection applications. In this paper, a group of Custom Designed Beams (CDB) are designed by radially encoding the multiple singular phases at the predefined locations to study the turbulence resistant property of these beams. Generation and propagation of these CDB are investigated in free space and the presence of atmospheric turbulence. The CDB are generated by a computer-generated hologram employing on the phase-only SLM. The ensquared energy of the CDB are calculated numerically and validated with the experimental results in free-space. Also, the effect of atmospheric turbulence on the propagation of the CDB is comprehensively investigated with the help of two types of turbulence simulators, atmospheric turbulence simulator and the turbulence cell, in the laboratory. A MATLAB based modified offline video processing method is used to compute all the relevant performance parameters. The effectiveness of these beams is determined by analyzing the beam deformation/spreading as beam spreading ratio and sensitiveness towards intensity fluctuation as scintillation index with reference to the conventional Gaussian beam. It is also reported that the CDB having multiple phase singularities at predefined configuration shows a significant decrease in the percentage of intensity fluctuations as compared to the Gaussian beam. Out of all the analyzed beams, the CDB of cases C14 and C15 show a significant reduction in scintillation index by 20–30% with more energy intact at the center. Thus, CDB of cases C14 and C15 would be proposed as the preferred design for laser projection applications.